Answer:
m∠5+m∠6=180°
m∠2+m∠3=m∠6
m∠2+m∠3+m∠5=180°
Explanation:
Verify each option
case A) we have
m∠5+m∠3=m∠4 ----> equation A
we know that
m∠3+m∠4=180° -----> by supplementary angles
m∠4=180°-m∠3 ----> equation B
substitute equation B in equation A
m∠5+m∠3=180°-m∠3
m∠5+m∠3+m∠3=180°
This equation is true when m∠2=m∠3
therefore
Is not always true
case B) we have
m∠3+m∠4+m∠5=180° ----> equation A
we know that
m∠3+m∠4=180° -----> by supplementary angles
m∠4=180°-m∠3 ----> equation B
substitute equation B in equation A
m∠3+(180°-m∠3)+m∠5=180°
m∠5=0°
This option is not true
case C) we have
m∠5+m∠6=180°
we know that
m∠5 and +m∠6 are supplementary angles
so
Their sum is always 180 degrees
therefore
This option is always true
case D) we have
m∠2+m∠3=m∠6 -----> equation A
we know that
m∠5+m∠6=180° ----> by supplementary angles
m∠6=180°-m∠5 ----> equation B
substitute equation B in equation A
m∠2+m∠3=180°-m∠5
m∠2+m∠3+m∠5=180°
Remember that the sum of the interior angles of a triangle must be equal 180 degrees
therefore
This option is always true
case E) we have
m∠2+m∠3+m∠5=180°
Remember that the sum of the interior angles of a triangle must be equal 180 degrees
therefore
This option is always true